2004
DOI: 10.1021/ef034082z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Asphaltene Aggregates Using X-ray Diffraction and Small-Angle X-ray Scattering

Abstract: X-ray diffraction (XRD) and small-angle X-ray scattering (SAXS) measurements were made on asphaltenes and vacuum residua (denoted by the prefixes As and VR, respectively) isolated from three different crude oilssMaya (MY), Khafji (KF), and Iranian Light (IL)sto characterize the petroleum asphaltene aggregates present under various conditions. In the XRD experiments, the samples were loaded on a small plate sample holder that was kept horizontal while measurements were made at 30, 150, and 300 °C. The layer dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
176
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(199 citation statements)
references
References 23 publications
18
176
0
Order By: Relevance
“…This suggests that when the natural bitumen is treated with a modifier, during the reaction asphaltene becomes more compact. These results are consistent with the results documented in the literature [6,17,20]. Similarly, average inter-chain layer distance (dc) also reduces from 4.63 to 4.4X Å (X = 2 or 4 or 6).…”
Section: X-ray Diffractionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that when the natural bitumen is treated with a modifier, during the reaction asphaltene becomes more compact. These results are consistent with the results documented in the literature [6,17,20]. Similarly, average inter-chain layer distance (dc) also reduces from 4.63 to 4.4X Å (X = 2 or 4 or 6).…”
Section: X-ray Diffractionsupporting
confidence: 93%
“…Due to the presence of high aromaticity, the Iranian light asphaltene precipitates comprehensively in decline even at lower temperature. In their other studies, Tanaka et al [6] reported a three main hypothetical aggression of asphaltene as (i) core aggregates are formed by p-p stacking of asphaltene molecules (20 Å size), (ii) medium aggregates are formed by secondary aggregation of core aggregates that result from interactions with maltenes, oils or solvents (50-500 Å) and (iii) fractal aggregates are secondary aggregates of core aggregates that results from diffusion limited cluster aggregation or reaction limited cluster aggregation (which is independent of any media) (size > 1000 Å). It was also concluded by the authors that this model of asphaltene aggregate was a highly simplified model.…”
Section: Introductionmentioning
confidence: 90%
“…Asphaltene aggregates transients from dimmers to stacked molecular nanoclusters of four monomers, which can be attributed to the strong interactions between asphaltene species when the asphaltene concentration range is from 10 to 300mg/L. In addition, many techniques have been used to investigate asphaltene aggregation, including surface tension measurements (Rogel et al, 2000), small-angle X-ray scattering measurements (Tanaka et al, 2004;Tanaka et al, 2003), atomic force microscopy (AFM; Toulhoat et al, 1994), and so on. Even though so many works have investigated these issues, few of them concentrated on giving the process of growth and development of asphaltene aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…XRD provides internal structural information and the crystallite parameters of the molecules associated in the aggregates. SAXS gives a topological view of the aggregate systems in which the X-rays are scattered by the electron density differences between the aggregate and the medium [15]. Since the asphaltenes are an extremely complex mixture of molecules, the use of a multidisciplinary approach through structure can be a useful means of investigating their chemical structure [4].…”
Section: Introductionmentioning
confidence: 99%